A Brief History of the Literature on Postmortem Changes to the 19th Century. Issue 1 (March 2016) - Milroy, Christopher M.
The fact that the body changes following death must have been known for the whole history of mankind. But myth and superstition surrounded the changes. This led to such entities as the ordeal of the bier being used as criminal proof, even though other forms of trial by ordeal had long been abandoned. The scientific literature in the English language did not start until the late 18th century and was still surrounded with ignorance and some superstition. The main concern of the early writers was the correct determination of death. In the 19th century, an understanding of postmortem changes developed and the first attempts to accurately classify sequences of putrefaction were made. This paper analyzes the early forensic medicine writing and the progress of knowledge to the later 19th century, through examination of forensic medicine textbooks published in the English language.